Knowledge Attitude and Practice towards Using Dental Magnification among Undergraduate Dental Students - Dr. M. Swetha, Dr. M. Swetha; Pratap, Dr. K. V. N. R.; Padma, Dr. T. Madhavi; Kumar, Dr. V. Srujan; Singh, Dr. Surbhit; Sri, Dr. S. Navya (International Journal Of Drug Research And Dental Science, 2025)
Dental magnification has revolutionized modern dentistry by improving visualization, precision, and overall treatment outcomes. The use of magnification tools such as loupes, and microscopes, allows clinicians to perform procedures with greater accuracy, reducing errors and enhancing patient care. Magnification improves ergonomics by promoting better posture, reducing fatigue, and minimizing strain-related musculoskeletal disorders. Additionally, it aids in early diagnosis, minimally invasive procedures, and improved documentation. Various levels of magnification cater to different dental specialties, with surgical microscopes offering the highest precision. Despite its numerous advantages, challenges such as cost, learning curve, and adaptation persist. However, as technology advances, dental magnification continues to play a crucial role in the evolution of high-quality dental care. Aim: To assess the knowledge, attitude, and practice towards using Dental Magnification among undergraduate Dental students. Objective: To Assess the Knowledge, attitude, and practice towards using dental Magnification among undergraduate dental students based on Gender. To assess the knowledge, attitude, and practice towards using dental Magnification among undergraduate dental students based on Year of study. Method: A cross-sectional survey was conducted among 215 dental students, comprising 76 males (35.3%) and 139 females (64.7%), including 52 second-year BDS students, 51 third-year BDS students, 60 fourth-year BDS students, and 52 interns. The survey included 15 questions exploring awareness, and perceptions, of dental students on Dental Magnification. Responses were analyzed based on gender and year of study using chi-square tests to identify statistically significant differences.